Removal of heavy metals from aqueous solution by sawdust adsorption - (:unkn) unknown (SCIENCE PRESS, 2007)
The adsorption of lead, cadmium and nicel from aqueous solution by sawdust of walnut was investigated. The effect of contact time, initial metal ion concentration and temperature on metal ions removal has been studied. The equilibrium time was found to be of the order of 60 min. Kinetics fit pseudo first-order, second-order and intraparticle diffusion models, hence adsorption rate constants were calculated. The adsorption data of metal ions at temperatures of 25, 45 and 60 degrees C have been described by the Freundlich and Langmuir isotherm models. The thermodynamic parameters such as energy, entropy and enthalpy changes for the adsorption of heavy metal ions have also been computed and discussed. Ion exchange is probably one of the major adsorption mechanisms for binding divalent metal ions to the walnut sawdust. The selectivity order of the adsorbent is Pb(II)approximate to Cd(II)> Ni(II). From these results, it can be concluded that the sawdust of walnut could be a good adsorbent for the metal ions from aqueous solutions.
Keywords: adsorption; heavy metals; sawdust; kinetic; thermodynamic parameters; METHYLENE-BLUE; SYNTHETIC SOLUTIONS; IONS; KINETICS; DECONTAMINATION; ADSORBENTS; MECHANISM; RECOVERY; SORPTION; DYE